2014
DOI: 10.1007/s00590-013-1400-1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical versus non-surgical management for primary patellar dislocations: an up-to-date meta-analysis

Abstract: The aim of this up-to-date meta-analysis was to compare the effects of surgical versus non-surgical treatment of patients following primary patellar dislocation and to provide the best evidence currently available. A comprehensive literature search was conducted using multiple databases, including Medline, Embase, and Cochrane Registry of Clinical Trials. All databases were searched from the earliest records to May 2013. Eligible studies were selected, and data were extracted by two independent investigators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 47 publications
1
44
2
Order By: Relevance
“…[11][12][13][14] These studies were published between 2011 and 2014, with all 4 performing a meta-analysis. One study reported a conflict of interest, 11 whereas 3 did not.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14] These studies were published between 2011 and 2014, with all 4 performing a meta-analysis. One study reported a conflict of interest, 11 whereas 3 did not.…”
Section: Resultsmentioning
confidence: 99%
“…Reviews without meta-analysis [32][33][34][35] recommended conservative treatment except in several specific circumstances, such as presence of osteochondral fractures. On the contrary, recent meta-analysis [37][38][39][40][41][42], showed that surgical treatment significantly reduces the risk of redislocation. Moreover, surgical treatment was shown to improve Hughston VAS [36][37][38]40] and Tegner [38,39] scores.…”
Section: Discussionmentioning
confidence: 96%
“…On the contrary, recent meta-analysis [37][38][39][40][41][42], showed that surgical treatment significantly reduces the risk of redislocation. Moreover, surgical treatment was shown to improve Hughston VAS [36][37][38]40] and Tegner [38,39] scores. Two papers [39,41] also reported higher Kujala score in short term (<5 years) follow-up, while evidence at six to nine years followup shifted towards conservative treatment.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations